THE EFFECT OF ISO 9001: 2015 QUALITY MANAGEMENT SYSTEM STANDARD IMPLEMENTATION TO IMPROVE THE QUALITY OF GRADUATES OF SMKS BINA SATRIA MEDAN: PENGARUH IMPLEMENTASI STANDAR SISTEM MANAJEMEN MUTU ISO 9001 : 2015 UNTUK MENINGKATKAN KUALITAS LULUSAN SMKS BINA SATRIA MEDAN - Pramana, Dodi; Eklesia Siringoringo, Rinca; Aulia Tasya, Khalisa (LPPM UPMI, 2023)
The research, entitled Analysis of the Implementation of Quality Management System Standards ISO 9001: 2015 to Improve the Quality of Graduates of SMKS Bina Satria Medan, aims to determine the effect of ISO 9001: 2015 on quality management systems and graduate production. The type of approach used in this study is a descriptive qualitative approach. The research location is SMKS Bina Satria Medan. The reason for choosing this location is because the school uses ISO 9001:2015 as its school's quality management system. Data collection techniques used are: observation, interviews, and documentation. The data analysis technique used is the Miles and Huberman Model, namely condensation, data presentation and conclusion/verification. The research results obtained are that with the implementation and management of ISO 9001: 2015 at international standard with adaptations to this matter, the presentation of quality in operational activities is in accordance with international standard conditions, thus helping BINA SATRIA SMKS to become a committed school, so that school management is increasingly recognized as able compete globally, thereby attracting trust in several parties, and more easily compete in competitive markets with international standard quality assurance. the application of ISO 9001:2015 has a positive impact towards improving the quality of graduates.